Science Problem-Solving Dynamics: Gender and Personality Type Analysis in Students - Sihombing, Rizky Agassy; Wahidin, Naufal Rabah; Rahmat, Adi; Winarno, Nanang; Hamdiyati, Yanti; Karimi, Amir (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
This study examines how problem-solving patterns in science among 9th-grade students correlate with different personality types based on Keirsey's classification: Idealist, Artisan, Guardian, and Rational. It employs the Investigation of Lived Experience methodology in Cognitive Psychology to delve into the internal experiences of 36 students from SMP Negeri 5 Bandung. The research explores gender distribution, school representation, and the prevalence of each personality type among the participants. Data collection methods include adapted questionnaires, written tests on earth and space science concepts, and follow-up interviews. These instruments are analyzed using the fixed comparison method to identify and understand distinct problem-solving tendencies associated with each personality type. Specifically, Idealists are found to prioritize understanding, Artisans employ intuitive-analogical approaches, Guardians rely on intuitive hypotheses, and rationalists utilize analogical reasoning. Overall, this study provides detailed insights into how personality types influence problem-solving strategies in science education. It suggests implications for personalized educational approaches tailored to individual student preferences and tendencies, aiming to enhance learning outcomes in 9th-grade science classrooms.